DRUG REPOSITION OF NON-CANCER DRUGS FOR CANCER TREATMENTS VIA PHARMACOVIGILANCE APPROACH - REPURPOSING DRUGS IN ONCOLOGY - PARMAR, MRUGANK; Panchal, Shital (Asian Journal of Pharmaceutical and Clinical Research, 2019)
This study for drug repositioning has been performed for the drugs which are in the market since more than a decade and they are approved with their well-established efficacy and safety in human being. Objective of this study was to reposition the existing non-cancer drug therapy for cancer treatment, which is having well characterized pharmacologic profile with more efficacy and least toxicity as anti-neoplastic agent. We have retrieved the source data from FDA Adverse Event Reporting System (FAERS) for the last 13 years covering duration from 2004 to 2016 and analysed those using pharmacovigilance approach â€˜a proposed future novel pharmaceutical tool for drug reposition’. Signal management activity was performed for statistical analysis. Result of statistical analysis derived that propranolol; metformin; pioglitazone; dabigatran and nitroglycerin are the existing non-cancer drugs which deserved for their direct / indirect reposition for cancer treatment and anti-neoplastic activity. Further studies retrieving the source data from other regulatory database (e.g. Eudravigilance of EMA and VigiFlow of WHO) and post-marketing surveillance study with the same objective may adjuvant our results for the reposition of existing drugs by pharmacovigilance approach.